Integracja Azji Wschodniej. Mit czy rzeczywistość? - Witczyńska, Katarzyna (East Asian Integration. Myth or reality?, 2009)
Today the globalized world influences political scientists who more and more often have an opinion that the region of East Asia has a great meaning for the world’s geopolitical situation. Thus, more researches focus on the economic and political integration of this region. The thesis that East Asia has a significant meaning for the world’s economic and geopolitical relations is unquestionable. Due to this fact, the region can compete with such “integrated organisms” like the United States or the European Union in many areas. The goal of this article is to analyze the problem of the East Asian integration process. The author is looking for an answer to the question if integration in this region is performed on the corresponding level as it is in the USA or EU - where economic, legal, social relations are equal, or it is only a myth due to various economic potentials?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 144-151